A cartografia escolar como metodologia na formação de professores de geografia na Universidade Estadual da Paraíba - Leite, Maria Adeni Clementino (2017)
In this dissertation we seek to analyze the School Cartography as methodology in the training of Geography teachers of the Universidade Estadual da Paraíba – UEPB, knowing that this institution offers the Geography course in Campus I – Campina Grande – and Campus III - Guarabira. Specifically, we contextualized the School Cartography in the teaching of Geography; we present the teachers' conceptions of the disciplines, focused on Cartography; we investigate and compare the students' understanding of the use of School Cartography in Geography classes. As a research methodology, we carried out a bibliographical survey based on theorists that approach the themes: Teacher training, curriculum, practice and teaching knowledge; School Cartography; among others. Thus, we used a semi-structured interview script and a questionnaire to collect data through the voluntary participation of three teachers - responsible for the Cartography disciplines - and forty-three students from the last semester of the course. Based on the data collected in this research, we observed that teachers configure their teaching practices in a bias directed to geographic technique, constituting in fragilities passed on to students in relation to the school discipline Geography, mainly in the use of cartographic knowledge. In addition, we understood how the use of School Cartography in the training of Geography teachers was given, and we identified that, despite the students having the opportunity to study subjects in the area of Cartography and access, however restricted, the materials demonstrated dissatisfaction with their Training, there is obviously a lack of preparation for teaching practice. Based on the discourses of the research subjects, we also identified problems related to infrastructure, time load, and teaching methodology of teachers. We also verified that the teachers interviewed need to rethink their practice and the importance of their role as teacher training future teachers, who present the responsibility to insert in their pedagogical practices new possibilities for the training of teachers for the teaching of Geography and the use of Cartography as a methodology for this training.